The Obstacles in Electronic Land Rights Registration and Their Solutions in land Sale and Purchase Cases - Yohanes; Rasji (Dinasti Research, 2024)
Abstract: This study analyzes the resolution of obstacles to electronic land rights registration in land sale and purchase cases. The rules in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 3 of 2023 concerning the issuance of electronic documents in land registration activities. This regulation regulates the issuance of electronic documents in land registration activities by setting limits on the terms used in its regulations. However, there are obstacles found in the implementation of land rights registration which were studied by the author using descriptive-analytical research methods, secondary data sources, and primary data, obtained from library research, and interviews with related parties. The results of this study are that land rights in the sale and purchase case cannot be registered because the buyer was declared dead shortly after the signing and there were registration obstacles in the PPAT account after confirmation to the relevant land agency, the heirs of the buyer are required to make a court decision. Keywords: Deed; Applicant; Official Certifier Of Title Deeds; Electronic Certificate.